Meningkatkan Kompetensi Guru dalam Menyusun Rencana Program Pembelajaran Harian Melalui Bimbingan Berkelanjutan Di Taman Kanak-Kanak Negeri Sari Mulya Kecamatan Rimbo Ilir Kabupaten Tebo Tahun 2021 - Srinduri Yatiningsih (Journal on Education, 2022)
This study aims to determine the improvement of teacher competence in preparing daily learning program plans through continuous guidance at the Sari Mulya Kindergarten, Rimbo Ilir District, Tebo Regency in 2021. teachers have complete and correct Components of Competency Standards reaching 81%, all teachers have listed the Basic Competence Components completely and correctly reaching 100%, all teachers have included the Components of Competency Achievement Indicators completely and correctly reaching 87%, all teachers have included the Objective Components Complete and correct learning reaches 87%, all teachers have included the Teaching Material Components completely and correctly reaching 100%, all teachers have included the Time Allocation Component completely and correctly reaching 100%, all teachers have included the Teaching Method Component Complete and correct lessons have reached 93%, all teachers have included the Components of Learning Activities Steps completely and correctly reaching 93%, all teachers have included Learning Resources Components completely and correctly reaching 100%, all teachers have included Learning Outcomes Assessment Components completely and correctly reached 75%. Thus the continuous guidance carried out by the Principal has an effective impact on increasing teacher competence in preparing Daily Activity Plans and is expected to have an impact on the learning process.